The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fendo.2022.1032361
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease across endocrinopathies: Interaction with sex hormones

Abstract: Nonalcoholic fatty liver disease (NAFLD) has emerged as the most frequent chronic liver disease globally. NAFLD is strongly associated with metabolic syndrome and it has been recently suggested that to rename NAFLD as metabolic dysfunction-associated fatty liver disease (MAFLD). NAFLD has been studied in different endocrine axes and accumulating body of clinical and experimental studies have suggested that NAFLD is associated with polycystic ovarian syndrome (PCOS), hypopituitarism, growth hormone deficiency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 208 publications
(374 reference statements)
0
4
0
Order By: Relevance
“…Previous research has demonstrated that there were significantly more females than males with MAFLD in age subgroups older than 40 years and there was a sharp rise in the prevalence of MAFLD in perimenopausal and postmenopausal women 26 , 27 , a period during which the decrease in oestrogen levels can lead to fat redistribution and lead to metabolic disorders, including MAFLD 28 . Furthermore, abdominal obesity in women is a well-documented risk factor for polycystic ovary syndrome(PCOS) while a number of studies have suggested the close correlation between PCOS and NAFLD 29 . A meta-analyze involving 7148 participants has reported that premenopausal PCOS patients are associated with 2.5-fold increase in the risk of NAFLD 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that there were significantly more females than males with MAFLD in age subgroups older than 40 years and there was a sharp rise in the prevalence of MAFLD in perimenopausal and postmenopausal women 26 , 27 , a period during which the decrease in oestrogen levels can lead to fat redistribution and lead to metabolic disorders, including MAFLD 28 . Furthermore, abdominal obesity in women is a well-documented risk factor for polycystic ovary syndrome(PCOS) while a number of studies have suggested the close correlation between PCOS and NAFLD 29 . A meta-analyze involving 7148 participants has reported that premenopausal PCOS patients are associated with 2.5-fold increase in the risk of NAFLD 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of dysregulations of endocrine axes (hypothyroidism, growth hormone deficiency, hypercortisolemia, etc.) are associated with NAFLD/fibrosis development and progression [96,97]. There are some suggestions that thyroid hormone levels are associated with the risk of progressive hepatic fibrosis in patients with T2DM, NAFLD, and normal thyroid function [98].…”
Section: Factors Associated With Fibrosis Progression and Regressionmentioning
confidence: 99%
“…NAFLD is considered as an umbrella term that includes different types of fatty liver diseases unrelated to alcohol consumption [ 4 ]. Due to the metabolic roots of NAFLD, it has been recently proposed that to rename NAFLD as metabolic dysfunction-associated fatty liver disease or 'MAFLD' [ 5 ]. A recent systematic review and meta-analysis through the extraction of available epidemiological data on fatty liver disease demonstrated that MAFLD has an astonishingly high prevalence rate in overweight and obese adults [ 6 ] .…”
Section: Introductionmentioning
confidence: 99%